CHARACTER EDUCATION IN TRANSLATION LEARNING AT UNIVERSITY OF QUALITY BERASTAGI - Jenita Anjani Sembiring (VISION, 2019)
This study was aimed at Integration of Character Education in Translation Learning At University Of Quality Berastagi. Everyone in general is never separated from education. Where through education human beings will get their true identity with every knowledge they get as long as they carry out education themselves. With the existence of character education that has a function to form each individual has a good character that is embedded in themselves from the beginning to lead to a better life so that he is beneficial to themselves and others in their environment. Self translation or often called Translation is a compulsory subject brought by students of English study programs. This eye is also inseparable from learning about anthropology, sociology, economics that is closely related to human life itself. Learning translation itself does not only focus on translating a language into another language, but also focuses on how we convey information from the source language to the target language without having to offend or misinterpret a particular party.